Resprouting of Acacia mearnsii stumps under different ages, seasons and cut heights - Perrando, Edison Rogério; Corder, Maisa Pimentel Martins (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of age, time of the year and cut height on the resprouting capacity of Acacia mearnsii De Wild. stumps. The work was conducted in stands of four and seven years of age, in randomized blocks design and time subdivided plots. Different cut heights (0.15; 0.30; 0.45; 0.60; 1.2 and 2 m), and evaluation times (15, 30, 45, 60, 75 and 90 days after cutting), in the four seasons of the year were evaluated. A significant interaction between cut height and evaluation time was found in both ages. The higher averages due to stumps in each strain were verified in 1.2 and 2 m height, in the age of four years. High death percentages were registered in seven years-old stumps, independently of cut height. The resprouting capacity of black wattle stumps is stimulated when cut is conducted between autumn and spring; summer is the least suitable season to stumps resprouting of this specie.